2012
DOI: 10.1111/j.2042-7158.2011.01430.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of marchantin C and fucoidan on sFlt-1 and angiogenesis in glioma microenvironment

Abstract: This study suggested for the first time that marchantin C and fucoidan could significantly inhibit angiogenesis induced by glioma cells or monocytes. Up-regulation of sFlt-1 played an important role in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
1
15
1
Order By: Relevance
“…Fucoidan was reported to suppress the growth pro-myeloid cancer cells [32], which supports the results of the present study that predicted effects of UPF on chronic and acute myeloid leukemias. Fucoidan has also been shown to affect the growth of glioma cells [30] and inhibit glioma cell-induced angiogenesis [33]. Fucoidans can act as both anti-angiogenic and pro-angiogenic agents, dependent mostly on their molecular weight [27], which was also identified by the present study.…”
Section: Discussionsupporting
confidence: 73%
“…Fucoidan was reported to suppress the growth pro-myeloid cancer cells [32], which supports the results of the present study that predicted effects of UPF on chronic and acute myeloid leukemias. Fucoidan has also been shown to affect the growth of glioma cells [30] and inhibit glioma cell-induced angiogenesis [33]. Fucoidans can act as both anti-angiogenic and pro-angiogenic agents, dependent mostly on their molecular weight [27], which was also identified by the present study.…”
Section: Discussionsupporting
confidence: 73%
“…Lv et al reported that fucoidan inhibited both T98G and THP1 cell-induced angiogenesis [32]. Proangiogenic molecules, such as bFGF, VEGF, and IL-8, play important roles in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Fucoidan, which is a sulphated polysaccharide purified from Sargassum , possesses a variety of anticancer effects, including the inhibition of the growth of HCC Huh7 cells and HepG2 cells, the induction of apoptosis and autophagy of human MCF-7 breast cancer cells, the Lewis lung carcinoma cells, melanoma B16 cells, and AGS human gastric adenocarcinoma cells, and the induction of the functional maturation of human monocyte-derived dendritic cells, T-cells, and natural killer cells [2631]. Lv et al reported that fucoidan inhibits both T98G and THP1 cell-induced angiogenesis [32]. However, the mechanisms of action through which fucoidan exhibits anticancer activity have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of fucoidan to work in synergy with standard anticancer agents has recently been investigated [20]. Fucoidan has shown to affect the migration and invasion of multiple myeloma (MM) cells treated with the chemotherapy drug cytarabine [493]. Human myeloma cell lines RPMI8226 and U266 were treated with crude fucoidan from F. vesiculosus for 72h followed by cytarabine for 6 h. Fucoidan reduced cell migration through a Boyden chamber and downregulated expression of CXCR4 and MMP-9.…”
Section: Fucoidan As a Synergistic Anticancer Agentmentioning
confidence: 99%